Signal transduction in chemotaxis to oxygen in Escherichia coli and Salmonella typhimurium. - Shioi, J (1988)
Pathways previously proposed for sensory transduction in chemotaxis to oxygen (aerotaxis) involved either (i) cytochrome o, the electron transport system, and proton motive force or (ii) enzyme IIGlucose and the phosphoenolpyruvate:carbohydrate phosphotransferase system for active transport. This investigation distinguished between these possibilities. Aerotaxis was absent in a cyo cyd strain of Escherichia coli that lacked both cytochrome o and cytochrome d, which are the terminal oxidases for the branched electron transport system in E. coli. Aerotaxis, measured by either a spatial or temporal assay, was normal in E. coli strains that had a cyo+ or cyd+ gene or both. The membrane potential of all oxidase-positive strains was approximately -170 mV in aerated medium at pH 7.5. Behavioral responses to changes in oxygen concentration correlated with changes in proton motive force. Aerotaxis was normal in ptsG and ptsI strains that lack enzyme IIGlucose and enzyme I, respectively, and are deficient in the phosphotransferase system. A cya strain that is deficient in adenylate cyclase also had normal aerotaxis. We concluded that aerotaxis was mediated by the electron transport system and that either the cytochrome d or the cytochrome o branch of the pathway could mediate aerotaxis.